The Effect of Educaplay on Learning Interest in IPAS at a Private Madrasah Ibtidaiyah - Virda Rahmat Kahayanti; Jumrodah Jumrodah; Muhammad Syabrina (Universitas Islam negeri Mahmud Yunus Batusangkar, 2026)
This study aimed to determine the extent to which the use of Educaplay media influences fourth-grade students’ learning interest in the IPAS subject. The research employed a quantitative approach using a pre-experimental method. The participants were 25 fourth-grade students of MIS Al-Jihad Palangka Raya. The study was conducted from November to January 2026 at MI Al-Jihad Palangka Raya. The results of data analysis revealed a positive and significant relationship between the use of Educaplay learning media (independent variable) and students’ learning interest (dependent variable). The correlation coefficient (R) was 0.607, which falls within the interval of 0.60–0.779 and is categorized as a strong correlation. The regression test results showed an F-value of 13.416 with a significance level of 0.001 < 0.05, indicating that the regression model is appropriate for predicting students’ learning interest based on the use of learning media. Furthermore, the coefficient of determination (R Square) was 0.368, indicating that the use of Educaplay media contributed 36.8% to students’ learning interest, while the remaining 63.2% was influenced by other factors beyond the scope of this study. Therefore, the alternative hypothesis (Ha) was accepted, confirming that there is a positive and significant relationship between the use of learning media and students’ learning interest